Disturbances in the field: Exhibiting Aboriginal art in the US. (June 2013) - Myers, Fred
This article considers the role of varied agents in the circulation of Papunya art across the relations between the Australian and the international art fields. My analysis follows an exhibition that took place at New York University's Grey Gallery in 2009, tracing in particular the international circulation of the highly valued 'early Papunya boards'. By focusing on the unsettled nature of Aboriginal art's circulation and the problem of producing its value socially in a world that is not consolidated, I consider Bourdieu's 'field of cultural production' as still becoming. Finally, my argument should caution against assuming that 'antipodean fields' might be addressed as autonomous from international agents, circuits of distribution and so on. It also questions Bourdieu's tendency to treat national art fields as independent.